Analisis Ruang Lingkup Sistem Bisnis Elektronik: Perspektif Teknologi, Proses Bisnis, dan Manajemen - Rio Rinto Saki; Antika Zahrotul Kamalia (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the scope of electronic business systems from the perspectives of technology, business processes, and management through a qualitative descriptive approach based on literature review. Data were collected from textbooks, scientific journals, and relevant empirical studies discussing the development and implementation of e-business systems in various organizational contexts. The analysis focuses on key aspects, including business models, technological infrastructure, data security and privacy, as well as human resources and change management. The findings indicate that electronic business systems represent an integrated framework that extends beyond online transactions to encompass internal process integration, strategic decision-making, and value creation. Effective implementation of e-business requires alignment between business models and market characteristics, supported by reliable technology and robust data protection mechanisms. In addition, organizational readiness, digital literacy, and adaptive management play a crucial role in ensuring successful digital transformation